Tax Avoidance and Corporate Risk: Does CSR Disclosure Make a Difference? - Hargiasto, Hartito; Firmansyah, Amrie (Indonesian Journal of Accounting and Governance, 2025)
Companies face various risks when carrying out their daily operational activities. One aspect that can increase this risk is the practice of tax avoidance. This study aims to evaluate the effect of tax avoidance on corporate risk, with corporate social responsibility (CSR) disclosure used as a moderating variable. This study focuses on coal mining companies listed on the Indonesian Stock Exchange from 2021 to 2023. Through the purposive sampling method, 36 observations were obtained as research samples. Data processing was carried out using linear regression to test the established hypotheses. The test results show that tax avoidance positively affects corporate risk, while CSR disclosure has been shown to weaken this relationship significantly. This finding is consistent with agency theory, which states that information asymmetry can encourage management to avoid taxes, and is in line with signaling theory, which emphasizes that CSR disclosure can minimize information asymmetry, thereby increasing investor confidence. Therefore, this study concludes that CSR disclosure can help reduce the risks arising from tax avoidance activities and be a reference for investors in making more appropriate investment decisions.